Gabon : First Review of the Extended Arrangement under the Extended Fund Facility, Requests for a Waiver for Nonobservance of Performance Criterion, and Modifications of Performance Criteria, and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for Gabon. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Gabon's First Review of the Extended Arrangement Under the Extended Fund Facility (EFF), Requests for a Waiver for Nonobservance of Performance Criterion (PCs) and Modifications of PCs, and Financing Assurances Review. The short-term outlook remains challenging. Although a growth rebound in 2018 is expected given recent developments in foreign direct investment inflows and better-than-previously projected activity in the oil and mining sectors, weaknesses in non-oil revenue collections and tight short-term liquidity conditions are sources of fiscal risk. The IMF staff supports the authorities' request for the completion of the first review, and modification of PCs for end-December 2017.